2020
DOI: 10.1111/apt.15904
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: early TIPSS in patients with cirrhosis and acute variceal bleeding—the plot thickens!

Abstract: Hence, these findings on absolute risk of pancreatic cancer are in fact reassuring of the low risk of pancreatic cancer in patients with IBD. The one group of patients that merits close attention are patients with PSC. The investigators observed a 7.5-fold higher risk of pancreatic cancer in patients with PSC-IBD as compared to patients without IBD or PSC, with a higher risk in patients with short-duration PSC (<5 years after PSC diagnosis). These findings are striking. It is probable that a substantial propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Furthermore, the "standard-of-care" for variceal bleeding has improved over the years with increasing use of potent nonselective beta-blocker such as carvedilol, endoscopic ligation, early transjugular intrahepatic portosystemic shunt and early access to the ICU. 38 These collective improvements may further dilute the survival benefit of antibiotic prophylaxis alone in cirrhosis patients with UGIB. In this study, we addressed this gap by reaffirming the survival benefit of prophylactic antibiotics in cirrhosis patients with UGIB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the "standard-of-care" for variceal bleeding has improved over the years with increasing use of potent nonselective beta-blocker such as carvedilol, endoscopic ligation, early transjugular intrahepatic portosystemic shunt and early access to the ICU. 38 These collective improvements may further dilute the survival benefit of antibiotic prophylaxis alone in cirrhosis patients with UGIB. In this study, we addressed this gap by reaffirming the survival benefit of prophylactic antibiotics in cirrhosis patients with UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…While antibiotics may reduce infection‐related mortality by preventing the risk of infection, none of the included studies reported infection‐related complications such as acute‐on‐chronic liver failure or hepatorenal syndrome following UGIB. Furthermore, the “standard‐of‐care” for variceal bleeding has improved over the years with increasing use of potent nonselective beta‐blocker such as carvedilol, endoscopic ligation, early transjugular intrahepatic portosystemic shunt and early access to the ICU 38 . These collective improvements may further dilute the survival benefit of antibiotic prophylaxis alone in cirrhosis patients with UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…It concluded that large multicentre RCTs are necessary to draw firm conclusions on survival benefit of TIPSS in all high‐risk groups. 34 …”
Section: Discussionmentioning
confidence: 99%
“…It concluded that large multicentre RCTs are necessary to draw firm conclusions on survival benefit of TIPSS in all high-risk groups. 34 The RA indication was also limited by the use of the single study by Bureau et al 11 to inform the majority of parameter values. Again, there were limitations with study size (n=62) and also generalisability of French data to the UK setting.…”
Section: Limitationsmentioning
confidence: 99%